Ultra high amorphous silicon passivation quality of crystalline silicon surface using in‐situ post‐deposition treatments. Issue 1 (5th December 2014) - Meddeb, H.; Bearda, Twan; Dimassi, Wissem; Abdulraheem, Yaser; Ezzaouia, Hatem; Gordon, Ivan; Szlufcik, Jozef; Poortmans, Jef
<x xml:space="preserve">Abstract</x> A parametric study of post‐deposition hydrogen plasma treatment of intrinsic a:Si:H films is performed. We demonstrate a significant improvement in passivation of c‐Si(100) promoting epitaxy after an in‐situ hydrogen plasma treatment depending mainly on the pressure and slightly on the power. Plasma diagnostic indicates an increase of Hα* signal with high power and low pressure. However, our analysis reveals a better hydrogen incorporation with high pressure and a slight increase in monohydride with high power. Longer H2 plasma duration up to 50 s shows no detrimental effect on the passivation quality. Optimizing the in‐situ H2 plasma treatment, high minority carrier lifetime over 15 ms was achieved after short thermal annealing. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)